Preparation and thermal decomposition of copper(II), zinc(II) and cadmium(II) chelates with 8-hydroxyquinoline - Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Greenhalf, Valentina C. M. [UNESP]; Zorel Jr., Henrique E. [UNESP] (Sociedade Brasileira de Química, 1999)
When the compounds are heated in an inert atmosphere it can be verified the consecutive partial sublimation, fusion, partial volatilization and partial thermal decomposition of the anhydrous complexes. When in an oxidating atmosphere the above process is only verified to Cu(II) chelates. Anhydrous copper(II) complexes present a monoclinic structure in the b form and the volatilized compound in a a form. Zinc(II) and cadmium(II) hydrated complexes are isomorphous and they present different cell dimensions from those reported previously.
Keywords: 8-hydroxyquinolinates; TG; DTA